Value Orientation of the Modern Studentship - I. V. Tarasevitch (Образование и наука)
The study is aimed at investigating the dynamics of students’ value orientation at the pedagogic higher school. The subject of the research incorporates the value-motivation sphere as being the component of students’ cognitive interest. The research methodology is based on the system determinism principle and combines the theoretical and practical substantiation of the value orientation problem as the main component of students’ cognitive interest. The research results referred to the professional activity values, growing year after year during the undergraduate course, can be taken into account in developing the value–motivation sphere of the studentship. The research shows that the proper psychological conditions created in the educational environment make the develop- ment of the value orientation system more successful.